(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article is devoted to the ideological and artistic features and composition of the epic "Farkhod and Shirin" from the epic "Khamsa" by Alisher Navoi, who lived and worked in the 15th century. This epic of Alisher Navoi differs from other epics in meaning and content.